F-Oligosac: a Biofunctional Prebiotic from Recombinant Aspergillus Niger Fermentation of Sago Starch - Mohd. Noor, Ahmad, Prof. Dr.; Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr.; Noor Hasyierah, Mohamad Salleh (C. I. S. Network, 2010)
Prof. Dr. Mohd. Noor Ahmad and his team from School of Bioprocess won bronze for F-Oligosac: a Biofunctional Prebiotic from Recombinant Aspergillus Niger Fermentation of Sago Starch. ITEX 2005, 19th - 21st May 2005 was held at Putra World Trade Centre (PWTC), Kuala Lumpur.